Optimum Frequency—Its Relevance and Measurements - Nataraja NP (Journal of All India Institute of Speech and Hearing, 1970)
This paper  discusses the importance of 'optimum pitch ' in  the  diagnosis and therapy with the  voice  disorders. The  merits and the  demerits of methods of measuring optimum pitch    and the  development of an objective method of locating optimum pitch have also been discussed. Experimental findings supporting that there  is  maximum physioacoustic economy  at  the optimum pitch as located by an objective method of locating  optimum pitch   have  been presented. An attempt has also been made to indicate  the possible  classification  of voice  disorders  based   on the  optimum  pitch